GIS in Sustainable Urban Planning and Management: A Global Perspective - van Maarseveen, M. (CRC Press, 2020)
Although this figure needs to be interpreted with caution due to inconsistencies in definitions and data availability, it emphasizes the urgent need to pay serious attention to this trend and to consider the positive and negative social, economic and environmental consequences carefully. Urbanization fosters economic growth and is generally associated with greater productivity and a better quality of life for all. Nevertheless, urbanization also often brings with it urban sprawl, environmental degradation, poor living conditions and severe problems of accessibility.